The determinant of Malaysia technology company profitability / Nur Atikah Ismail - Ismail, Nur Atikah (2022)
This research aims to identify the determinants of Malaysia's Technology company profitability. Technology is essential not only for the economy, but also for dealing with advanced development. Every year, technological advancements have increased the importance of the technology sector in every country, making it a critical business platform. One of the industries that is seeing an uptick in customer trust is technology. When there is an Industrial Revolution (IR) 4.0, technology-related industries seem to be revolute. Furthermore, Covid-19 has increased the role of the technology in the fight against the pandemic. It allows the IT industry to continue to flourish in the face of the pandemic. The relationship between return on current ratio, debt-equity ratio, and net working capital is analysed using Return on Asset (ROA). The data for this analysis came from the annual reports of the sampled companies as well as Refinitive Eikon. This research is based on secondary data from five (5) technology companies that were listed on Bursa Malaysia between 2010 and 2020. D&O, FRONTKN, MYEG, PENTA, and VITROX are the technological companies chosen for this study. The expected findings for this research are that all the independent variables are significant to the dependent variables.